Determinan Karakteristik Status Kelayakan Rumah di Provinsi DKI Jakarta Tahun 2022 - Ferdiansyah, Dicky; Utami, Efri Diah (Politeknik Statistika STIS, 2023)
DKI Jakarta contributes the largest GRDP to national economic growth in 2022. This condition is supported by the average net monthly formal worker’s wage/salary, the average net monthly informal worker’s income, the Regional Minimum Wage, and HDI that all being the highest in Indonesia. However, in 2022, there are 63.77 percent of DKI Jakarta’s households access unlivable houses. House construction considers social and economics factors. This research uses Susenas data of March 2022 for descriptive analysis through graphics and inferential analysis through binary logistic regression. The results show that households that tended to access livable houses have household heads with minimum senior high school education and older ages, have monthly per capita expenditure of minimum IDR 1.9 million, non-recipients of credit, and occupy their homes. This research is expected to identify the household characteristics that access livable houses and help to determining policies regarding the issue of livable housing’s access.